ADVANCING LIFELONG LEARNING: INTEGRATING NON-STANDARD TASKS IN PHYSICS EDUCATION - Baratov Jurakuzi Shukurjon ugli (Western European Studies, 2024)
This article focuses on enhancing teaching methodology through an integrative approach, emphasizing the application of non-standard assignments within the physics curriculum. The study specifically addresses the integration of these assignments into the education of future educators in pedagogical higher education institutions. The article underscores the significance of this approach in elevating the professional training of prospective teachers, expanding students' knowledge, fostering interdisciplinary thinking, and stimulating interest in science. The research also delves into the development of a methodical system that incorporates problems, tests, and non-standard assignments, aiming to improve students' understanding of physics while highlighting interconnections with geography, biology, chemistry, and fostering a holistic approach to learning
Keywords: non-standard tasks related to the topic; reproductive; productive